Respiratory Variations in Aortic Blood Flow to Predict Volume Responsiveness in Ventilated Children With Leukemia and Neutropenic Septic Shock*. Issue 5 (May 2020) - Sun, Sijuan; Ren, Hong; Wang, Ying; Zhang, Jian; Li, Biru; Ning, Botao; Qian, Juan
Abstract : Objectives: To investigate whether respiratory variations in aortic blood flow by echocardiography can accurately predict volume responsiveness in ventilated children with leukemia and neutropenic septic shock. Design: A prospective study. Setting: A 25-bed PICU of a tertiary hospital. Patients: Mechanically ventilated children with leukemia who had been exposed to anthracyclines and exhibited neutropenic septic shock were enrolled. Interventions: Transthoracic echocardiography was performed to monitor the aortic blood flow before and after fluid administration. Measurements and Main Results: After volume expansion, left ventricular stroke volume increased by greater than or equal to 15% in 16 patients (responders) and less than 15% in 14 patients (nonresponders). The performance of respiratory variation in velocity time integral of aortic blood flow and respiratory variation in peak velocity of aortic blood flow for predicting volume responsiveness, as determined by the area under the receiver operating characteristic curve, was 0.74 (95% CI, 0.55–0.94; p = 0.025) and 0.71 (95% CI, 0.53–0.90; p = 0.048), respectively. Positive end-expiratory pressure was higher in nonresponders than in responders ( p = 0.035). Conclusions: Respiratory variation in velocity time integral of aortic blood flow and respiratory variation in peak velocity of aortic blood flow derived from transthoracic echocardiography showed only a fair reliability in predicting volume responsiveness in ventilated children with leukemia and neutropenic septic shock.